Practical considerations for implementing an evidence-based policing approach in police operations: a case study - Kadry, Ahmed Tarek (Policing and society, 2021)
Through the lens of a real operation carried out at Greater Manchester Police to protect the business community from burglaries over the Christmas and New Year period in 2017/2018, this paper highlights the practical considerations in implementing an evidence-based approach in policing operations where there is a perceived immediate threat, risk and harm. Operation Guard was a force-wide operation that ran for four months (1st December 2017–30th March 2018 inclusive) across seven districts and eleven wards in Greater Manchester (UK), with the primary mandate of reducing Greater Manchester Police’s (GMP) commercial burglary crime volume. With the operation carrying a second aim of tactical delivery through an evidence-based policing methodology, representing the first of its kind at this scale at GMP, this paper highlights key practical considerations and learning opportunities for future tactical deployment for both police strategic and tactical leaders, as well as policing academics.